Photolytic properties of cobalamins: a theoretical perspective. Issue 11 (11th February 2016) - Kozlowski, Pawel M.; Garabato, Brady D.; Lodowski, Piotr; Jaworska, Maria
Abstract : This Perspective Article highlights recent theoretical developments, and summarizes the current understanding of the photolytic properties of cobalamins from a computational point of view. Abstract : This Perspective Article highlights recent theoretical developments, and summarizes the current understanding of the photolytic properties of cobalamins from a computational point of view. The primary focus is on two alkyl cobalamins, methylcobalamin (MeCbl) and adenosylcobalamin (AdoCbl), as well as two non-alkyl cobalamins, cyanocobalamin (CNCbl) and hydroxocobalamin (HOCbl). Photolysis of alkyl cobalamins involves low-lying singlet excited states where photodissociation of the Co–C bond leads to formation of singlet-born alkyl/cob(ii )alamin radical pairs (RPs). Potential energy surfaces (PESs) associated with cobalamin low-lying excited states as functions of both axial bonds, provide the most reliable tool for initial analysis of their photochemical and photophysical properties. Due to the complexity, and size limitations associated with the cobalamins, the primary method for calculating ground state properties is density functional theory (DFT), while time-dependent DFT (TD-DFT) is used for electronically excited states. For alkyl cobalamins, energy pathways on the lowest singlet surface, connecting metal-to-ligand charge transfer (MLCT) and ligand field (LF) minima, can be associated with photo-homolysis of the Co–C bond observed experimentally. Additionally, energy pathways between minima and seams associated with crossing of S1 /S0 surfaces, are the most efficient for internal conversion (IC) to the ground state. Depending on the specific cobalamin, such IC may involve simultaneous elongation of both axial bonds (CNCbl), or detachment of axial base followed by corrin ring distortion (MeCbl). The possibility of intersystem crossing, and the formation of triplet RPs is also discussed based on Landau–Zener theory.